KRISTIJONAS DONELAITIS AND PETTER DASS – PARALLEL PIONEERS IN LITHUANIAN AND NORWEGIAN POETRY - VISTDAL, OSKAR (Knygotyra, 2015)
This paper aims to identify links between “The Seasons” and Scandinavian poetry. Contemporary connections are hardly demonstrable, but a striking older parallel is Petter Dass’ epic poem “Nordlands Trompet” (The Trumpet of Nordland, 1678–1696, published posthumously in 1739), the most important pre-romantic literary work in Norway. In many ways its position is parallel to Donelaitis’ “Seasons”: both poems mark the beginning of modern literature in Norway and Lithuania, respectively – emonstrating the literary potential of the poets’ mother tongues and paving the way for the national literature of future generations. Conspicuous are also “The Trumpet’s” numerous parallels with “The Seasons”in moods and motifs, modelled by common aesthetic taste and literary modes. “The Trumpet” is a versified topographical encomium in anapaestic meters. Just like “The Seasons”, Petter Dass’ poem describes everyday life, natural and commercial conditions. It is a thematic description of the Arctic part of Norway, its location, astronomical and meteorological conditions, birdlife, fish and whales, agriculture, market places, and ethno-cultural peculiarities, i.e. manners and modes of living among the Sami or Lapp people. “The Seasons” and “The Trumpet” are both major contributions to European literature, describing nature, living conditions and culture in relative proximity in ways that show their close affinity in spite of considerable differences of life and conditions in Baltic fields and forests and on Arctic seas and shores.